Sperm Response to in vitro Stress Conditions in Wild and Domestic Species Measured by Functional Variables and ROS Production - O'Brien, Emma; García-Casado, Pedro; Castaño, Cristina; Toledano-Díaz, Adolfo; Bóveda, Paula; Santiago-Moreno, Julián (Frontiers in Veterinary Science, 2021)
The success of assisted reproductive technologies in both domestic and wild species, including artificial insemination, depends on the sperm resistance to dilution, incubation and refrigeration storage in vitro conditions. The domestication process has modified the reproductive physiology through changes in annual endocrine changes and breeding seasonality. It is expected that domestication has also modified membrane sperm composition and sexual accessory glands function that may affect sperm response to chilling. The first objective of this study was to examine the sperm response to a cooling-storage and subsequent incubation in different species of domestic and wild ungulates. The second one was to detect which sperm variables best explain the variability when subjecting the sperm to stress by cold storage and subsequent incubation. Sperm samples from six different species (domestic and their respective wild ancestors) were used: boar (Sus scrofa domestica) vs wild boar (Sus scrofa), ram (Ovis aries) vs mouflon (Ovis musimon), buck (Capra hircus) vs ibex (Capra pyrenaica). Sperm motility, viability, mitochondrial membrane status, DNA fragmentation and reactive oxygen species production were evaluated before and after refrigeration at 15°C for 20 h and subsequent incubation at 38.5°C, 5% CO2, for 2 h. Sperm from all domestic species suffered more stress than their wild relatives. In pigs, the percentage of intact mitochondria was lower in the domestic species compared to wild boar. In sheep, we found a higher reactive oxygen species production in ram, while in goats, the curvilinear velocity was lower in the domestic species. In addition, we performed a principal components analysis (PCA) to reduce the dimensionality of a set of variables while retaining the maximum variability. The PCA showed that the motility and their kinetic variables were the most represented variable in the principal components of all species, indicating that it is an essential biomarker for evaluating the stress response. Sperm viability highlighted as representative variable for evaluating the stress response in domestic boar, mouflon, ram and ibexes.